Pengaruh Pengetahuan Pajak, Kesadaran Wajib Pajak, Sanksi Pajak, Akuntabilitas Pelayanan Publik dan Tarif Pajak Terhadap Kepatuhan Wajib Pajak Dalam Membayar Pajak Kendaraan Bermotor di Kantor Samsat Singaraja - Dewi, Ida Ayu Putu Priska; Yudantara, I Gede Agus Pertama (Universitas Pendidikan Ganesha, 2020)
The purpose of this research was to find out the effect of tax knowledge,Â taxpayer awareness, tax sanction, public service accountability and tax rate on taxpayer compliance. This research used quantitative approach in which it was done at One Roof System Office Buleleng Regency. In taking samples,Â the researcher applied Insidental Sampling as the method thus there were 100 respondents obtained as the sample. The research data was collected by using questionnaire then those processed with multiple linear regression analysis test by using SPSS 22 version. The result of this research was all of the independent variables had significant effect on taxpayer compliance thus the hypothesis in this study can be accepted. The researcher also found that the most influential variable on taxpayer compliance was public service accountability. This was because public service accountability at One Roof System Offive Buleleng has provided adequate services, satisfying services, resolving problems quickly and understanding the existing regulations